Code Switching and Code Mixing in Film "Tokyo Fiancee" - Desmi Khoirotunnisak; Eka Fanti Sulistiyaningsih (Journalistics: Journal of English Teaching and Applied Linguistics, 2022)
This research aims to: (1) examine and describe the code switching and code mixing inside the film Tokyo Fiancée by Stefan Liberski; (2) examine and describe the varieties of utterances code switching and code mixing inside the movie Tokyo Fiancée by Stefan Liberski; (3) discover the influential factors of code switching and code mixing within the movie. Descriptive qualitative became hired as a research layout of this have a look at with records playing cards as the research instruments adapted from the theories of Poplack (1980), Muysken (2000), Suwito (1983, 1985) and Eunhee (2006). The findings of this study at discovered that the film used three languages in oral speech including Japanese, French, and English. Among those oral speeches, there have been sixty nine utterances containing code switching this is protected in 3 types, specifically tagswitching, inter-sentential switching and intra-sentential switching. Then, those 39 utterances protected code mixing this is included in 5 kinds, specifically insertion code mixing, alternation code mixing, congruent lexicalization code mixing, inner code mixing and outer code mixing.